Prior Knowledge and Its Effect on Comprehension - Langer, Judith A.; Nicolich, Mark ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1980)
Based on the view that text-specific concept and vocabulary knowledge affect the processing and recall of text and that a measure of this knowledge might assist teachers in determining whether a reader possesses adequate background to successfully comprehend and recall a particular text, a study was conducted. Its purpose was to develop a measure that reflects the strength of organization of existing knowledge as it relates to key concepts and vocabulary in content area textbooks. The study elicited prior knowledge from 36 high school seniors, using free association based on stimulus content words from reading passages, categorized this knowledge into broad levels, and statistically examined the nature of the relationships between these assigned levels of prior knowledge and the organization of recall. The findings indicated that level of prior knowledge was strongly related to the recall of a passage as measured by B. J. F. Meyer's analysis of prose. In addition, it was found that the relationship among recall measures and between level of prior knowledge and the recall measures was dependent on the passages used, indicating that there was some passage dependency in terms of both prior knowledge and recall. (FL)
ERIC Note: Paper presented at the Annual Meeting of the International Reading Association (25th, St. Louis, MO, May 5-9, 1980).
Educational level discussed: Secondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Content Area Reading; Discourse Analysis; Knowledge Level; Readability; Reading Comprehension; Reading Difficulties; Reading Materials; Reading Processes; Reading Research; Reading Tests; Recall (Psychology); Secondary Education; Test Construction; Textbook Content; Reports, Research; Speeches/Meeting Papers